Implementasi Sistem Pendukung Keputusan Penentuan Siswa Berprestasi Menggunakan Metode Simple Additive Weighting (SAW) pada SMK Negeri 1 Raman Utara (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Recognizing outstanding students is an essential strategy to encourage learners to improve their academic performance and overall learning quality. However, the process of selecting the best students at SMK Negeri 1 Raman Utara still encounters significant challenges due to the complexity of the evaluation criteria, which include academic achievement, attendance, participation in extracurricular activities, and student behavior. The current manual selection method is considered less effective because it is time-consuming and susceptible to subjectivity in decision-making. This study aims to address these issues by developing a technology-based Decision Support System utilizing the Simple Additive Weighting (SAW) method. SAW was chosen for its efficiency in solving multi-criteria problems through matrix normalization and preference weighting for each alternative. The development process includes requirement analysis, system design, and the implementation of an automated ranking mechanism for student candidates. Based on the testing results, the implemented system can process assessment data rapidly and produce accurate and objective rankings of high-achieving students. The system offers a practical solution for the school by enhancing transparency and validity in the selection process, minimizing human calculation errors, and supporting more equitable and data-driven decision-making.